PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. AWOT GLOBAL LOGISTICT CABANG CIRENDEU - Tiara Avrianisa; Uswatun Chasanah (Journal of Research and Publication Innovation, 2025)
This research aims to find out the influence of Work Discipline and Work Motivation on Employe Performance at PT. AWOT Global Logistict Cirendeu branch. Hypothesis testing uses associative research design, statistical analysis methods consisting of multiple linear regression alaysis, partial testing (t-test) and cofficient of determination testing. The results of this tesearch were partial testing (t-test). Shows that the Work Discipline variable has a positive and significant effect on the Employee Performance, the Work Motivation variabel together (simultaneously) have a positive and significant effect on the Employee Performance variable, with a value of Fcount > Ftable (43,024 > 3,18) with a significance value of (0,000 > 0,05). And through the coefficient of determination test a value of 59,8% was obtained, meaning that these result show that the contribution of Work Discipline and Work Motivation result to the Employee Performance variabel is 59,8% and the total sample was 55 employees.